PENINGKATAN HASIL BELAJAR MATEMATIKA SMP MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Khofipah, Siti; Setiawan, Wahyu; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Through the use of Realistic Mathematics Education (RME) approach, this activity seeks to improve mathematics learning outcomes. This research uses classroom action research as its methodology. At An-Naja Middle School, this research was conducted. The sample of this study amounted to 15 students, and the implementation took place in November. RPP, LKPD, and description exam questions are research tools used. The written test data processing technique in this study used the percentage. The results showed that 1) by using the RME approach, student learning outcomes have increased as indicated by the increase in student learning success, where the average value of students in the first cycle is 38.80 with a percentage of 6.6% and increased to 89.40 with a percentage value of 100 % in cycle II. The application of the method can be concluded from the research findings. The application of realistic mathematics teaching strategies can improve student learning outcomes.